2008
DOI: 10.1627/jpi.51.191
|View full text |Cite
|
Sign up to set email alerts
|

Search for Unified Action Mechanism of Hindered Amine Light Stabilizers

Abstract: Hindered amine light stabilizers (HALS) possess many functions unlike other additives and are frequently used to extend the service life of polymeric materials, but show particular compatibility with certain other additives. However, combination does not always show synergistic actions, but sometimes has antagonistic effects. Most previous research into the interaction of HALS with other additives has focused on qualitative high synergism to high antagonism, and no common understanding has been reached. HALS a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…According to other investigations, this is due to the primary phenolic antioxidant becoming increasingly acidic, which interacts with the alkaline environment of the hindered amine stabilizer. The resulting antagonistic acid/base mechanism, which involves the consumption of phenol by the activated hindered amine stabilizer, is also discussed in literature [48,49,50]. Moreover, this may be related to the insufficient compatibility of the stabilizer with the base polymer, which leads to the stabilizer aggregates at inter-spherulitic boundaries acting as inherent defects.…”
Section: Resultsmentioning
confidence: 99%
“…According to other investigations, this is due to the primary phenolic antioxidant becoming increasingly acidic, which interacts with the alkaline environment of the hindered amine stabilizer. The resulting antagonistic acid/base mechanism, which involves the consumption of phenol by the activated hindered amine stabilizer, is also discussed in literature [48,49,50]. Moreover, this may be related to the insufficient compatibility of the stabilizer with the base polymer, which leads to the stabilizer aggregates at inter-spherulitic boundaries acting as inherent defects.…”
Section: Resultsmentioning
confidence: 99%
“…This acid/ base mechanism leads to the quinoid structures observed. The antagonistic mechanism involving this useless consumption of the phenol by the NO•e compound is frequently discussed in the literature [6,12]. In these investigations either ESR-spectroscopy or GC was used for monitoring the transformation of the individual species.…”
Section: Behavior Of Tinuvin 770 In the Presence Of Phenolic Antioxidmentioning
confidence: 99%
“…Hindered amine light stabilizers (HALS) have been used widely as antioxidants . They were originally developed as light stabilizers, but now they are also used as multifunctional additives, since they have been found to work as a radical‐trapping agent, a heavy metal deactivator, a hydroperoxide decomposer, and so on . The HALS and phenolic antioxidants are frequently used together practically , but previous studies have shown either antagonism or synergism .…”
Section: Introductionmentioning
confidence: 99%